2013
DOI: 10.3140/bull.geosci.1411
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Eocene–Oligocene transition: a case study from North Bohemia

Abstract: Geology and palaeontology of the Roudníky area, situated between the Most Basin and the České středohoří Mountains in North Bohemia, the Czech Republic, is treated in detail. The volcano-sedimentary structure underlying the basin with the included fossiliferous layers is newly interpreted as a maar-diatreme. The radiometric age of the basalts was determined to 35.4 ± 0.9 Ma and 37.1 ± 0.9 Ma -late Eocene, Priabonian. The fish fauna consists of amiids characteristic of other adjacent late Eocene sites while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 29 publications
6
27
0
Order By: Relevance
“…However, it has repeatedly been stated that the examined floras indeed indicate differences in the annual distribution of precipitation, but summer drought or "aridity" has never been confirmed by any quantitative study (Table 2). Recently, Kvaček et al (2014) indicated again similar results with 541 mm (3WET) and 86 mm (3DRY) for the late Eocene flora of Knau that is also a site in the Weißelster Basin and the Zeitz FA (Mai and Walther, 2000). Furthermore, it must be questioned whether notophyllous broad-leaved forests could be established in a period when main growing seasons coincide with drought or "aridity".…”
Section: Palaeoclimate Signals For the Zeitz Fasupporting
confidence: 51%
See 4 more Smart Citations
“…However, it has repeatedly been stated that the examined floras indeed indicate differences in the annual distribution of precipitation, but summer drought or "aridity" has never been confirmed by any quantitative study (Table 2). Recently, Kvaček et al (2014) indicated again similar results with 541 mm (3WET) and 86 mm (3DRY) for the late Eocene flora of Knau that is also a site in the Weißelster Basin and the Zeitz FA (Mai and Walther, 2000). Furthermore, it must be questioned whether notophyllous broad-leaved forests could be established in a period when main growing seasons coincide with drought or "aridity".…”
Section: Palaeoclimate Signals For the Zeitz Fasupporting
confidence: 51%
“…Both areas, the coastal and riparian habitats of the Weißelster Basin as well as the Bohemian "hinterland" including volcanic environments, feature a similar floristic composition, determined by using the integrated plant record vegetation analysis (IPR-vegetation analysis) which indicates the occurrence of broad leaved evergreen forests for both regions (Kvaček et al, 2014).The Bohemian flora of Roudníky (35.4 ± 0.9 Ma) is an exception as it mirrors the gradual change towards mixed mesophytic forests (MMF) by immigration of deciduous, temperate taxa and stepwise extinction of subtropical and tropical plants, and thus the proceeding global cooling trend towards the EOT. The flora of Roudníky shows MAT ranges of 13.6-18.0°C with CA and 10.0 ± 1.3°C determined by CLAMP (Kvaček et al, 2014). No flora corresponding to Roudníky is currently known from the latest Eocene of the Weißelster Basin.…”
Section: Transregional Significance Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations